2020
DOI: 10.3389/fpls.2020.581140
|View full text |Cite
|
Sign up to set email alerts
|

Root Architecture and Functional Traits of Spring Wheat Under Contrasting Water Regimes

Abstract: Wheat roots are known to play an important role in the yield performance under water-limited (WL) conditions. Three consecutive year trials (2015, 2016, and 2017) were conducted in a glasshouse in 160 cm length tubes on a set of spring wheat ( Triticum aestivum L.) genotypes under contrasting water regimes (1) to assess genotypic variability in root weight density (RWD) distribution in the soil profile, biomass partitioning, and total water used; and (2) to determine the oxygen and hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 111 publications
1
9
0
Order By: Relevance
“…Based on this idea, this study examined the root morphology of eight L. siceraria genotypes and investigated the various root traits at different substrate depths and root diameter intervals under a water-deficit condition. For instance, different root-related traits, such as primary root length, number and length of lateral roots, and average root diameter, have been proposed as important traits that contribute to regulating water uptake, which is critical under drought stress (Gorim and Vandenberg, 2017 ; Mwenye et al, 2018 ; Brunel-Saldias et al, 2020 ; Gao et al, 2020 ). In this study, a statistically significant effect of water deficit was reported over all the evaluated root traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this idea, this study examined the root morphology of eight L. siceraria genotypes and investigated the various root traits at different substrate depths and root diameter intervals under a water-deficit condition. For instance, different root-related traits, such as primary root length, number and length of lateral roots, and average root diameter, have been proposed as important traits that contribute to regulating water uptake, which is critical under drought stress (Gorim and Vandenberg, 2017 ; Mwenye et al, 2018 ; Brunel-Saldias et al, 2020 ; Gao et al, 2020 ). In this study, a statistically significant effect of water deficit was reported over all the evaluated root traits.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gorim and Vandenberg ( 2017 ) pointed out that, between depths of 40–60 cm, lentil genotypes with higher total root length (TRL) proportions of very fine roots (<0.5 mm) were able to exploit both water and nutrients more efficiently; while between depths of 0–20 and 20–40 cm, lentil genotypes with TRL diameters >2.0 mm were more efficient in the long-distance transportation of water and nutrients. Similarly, Brunel-Saldias et al ( 2020 ) showed that, under a water-limited regime, water use (WU) in spring wheat was positively related to root weight density at different soil layers. Thus, while root traits such as length, diameter, area, and volume are important, more information about root systems can be gained by looking at root distribution patterns at various soil depths.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the future, the selection of new cultivars should be based on a complete phenotypic and genetic description of the materials to be used as parental material in breeding programs. This can be based on new high-throughput phenotyping techniques [ 163 ], such as the characterization of plant canopy temperature and root system architecture in heat and drought stress experiments [ 164 ]. The whole genetic characterization of parent material should be one of the cornerstones in the future.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Among many factors that reduce the efficiency of grain production, overlooking an arsenal of phytophages and phytopathogens developing, which significantly hampers yield growth, subject to specific natural and climatic conditions and closely related crop production processes, is fatal. A more flexible approach in framing the strategy, feasibility and agenda of measures to protect crops will not only increase the yield of winter wheat, but also reduce the environmental risks associated with an unwarranted use of pesticides [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%